PEMODELAN DAN SIMULASI ON-GRID PHOTOVOLTAIC DENGAN GRID-TIED INVERTER MENGGUNAKAN MATLAB/SIMULINK - Sungkalang, Sripanus Sungkalang; Silalahi, Eva Magdalena; Widodo, Bambang (Lektrokom : Jurnal Ilmiah Teknik Elektro, 2023)
Solar power plants are one of the environmentally friendly renewable energy generators because they utilize sunlight, which can be absorbed by photovoltaic (PV). The purpose of this study is to create and analyze on-grid photovoltaic modeling and simulation using a grid-tie inverter based on MATLAB/Simulink, and then to analyze the quantity of PV electricity based on real time data of solar irradiation and temperature. Based on the modeling and simulation results, the characteristics of the on-grid PV system are obtained, namely: constant V, I and P waveforms in the form of straight lines on 1 100 Wp PV module, at a constant value of 1000 W/m2 solar irradiation and a temperature of 25°C, with V = 18V, I = 5.55A, and P = 100W. On 10 PV modules with solar irradiation values and real time temperatures, the V, I and P waveforms were obtained following the solar irradiation pattern, with Vmax = 34.91V, Imax = 26.92A and Pmax = 939.7W at 11.00-12.00 noon, when the peak solar irradiation reaches 954 W/m2. It is also obtained that the maximum PV power is 940 W at 11.00 – 12.00 noon and the average power is 291 W. The peak power of the grid is 1.185 W, with an average power of 588 W. The peak load of electricity consumption is 1.128 W at 08.00 at night, with load power average 596 W. Overload PV = 1950 W.